2020
DOI: 10.1186/s40478-020-00948-z
|View full text |Cite
|
Sign up to set email alerts
|

Humanized tau antibodies promote tau uptake by human microglia without any increase of inflammation

Abstract: Immunotherapies targeting pathological tau have recently emerged as a promising approach for treatment of neurodegenerative disorders. We have previously showed that the mouse antibody DC8E8 discriminates between healthy and pathological tau, reduces tau pathology in murine tauopathy models and inhibits neuronal internalization of AD tau species in vitro. Here we show, that DC8E8 and antibodies elicited against the first-in-man tau vaccine, AADvac1, which is based on the DC8E8 epitope peptide, both promote upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…Moreover, microglia are reported to have different regional abundance and activity states during aging, brain activity and neurodegenerative processes ( 58 , 70 72 ). In addition, accessing microglia in the human brain is in the majority of cases only possible in postmortem tissue ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microglia are reported to have different regional abundance and activity states during aging, brain activity and neurodegenerative processes ( 58 , 70 72 ). In addition, accessing microglia in the human brain is in the majority of cases only possible in postmortem tissue ( 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that an effective therapeutic antibody should eliminate pathological tau proteins from the diseased brain, the effector function of such antibody becomes desirable. Our preclinical data with therapeutic anti-tau antibody AX004 indicate that IgG1 antibodies (with effector function) are more effective in facilitating the uptake of extracellular abnormal tau by adult human microglia than the IgG4 isotype (Zilkova et al 2020). Moreover, no safety signals have been observed throughout the course of the AADvac1 phase 1 and phase 2 clinical trials, although AADvac1 vaccination generated predominantly IgG1 antibody response in AD patients (Novak et al 2018).…”
Section: Discussionmentioning
confidence: 87%
“…This approach eliminates potential unfavourable effect of microglia activation but at the same time desirable tau clearing properties. In summary, tau-targeting vaccines recognize different tau species and have been suggested to act through various mechanisms: by preventing tau aggregation and cell-to-cell spreading (Theunis et al 2013;Albayram et al 2017;Courade et al 2018;Novak et al 2018;Albert et al 2019;Weisova et al 2019), by facilitating tau uptake by microglia (Zilkova et al 2020) and endo-lysosomal degradation of tau in microglia (Andersson et al 2019) or proteasomal degradation of tau seeds in neurons (McEwan et al 2017).…”
Section: The Role Of Microglia In Tau Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…When delivered with SUS +MB , RNF5 was only internalised into degenerating neurons and this is in line with other publications that have shown that antibodies are not readily internalised into neurons [25] or are only detected in dying neurons [27] which presents the possibility that RNF5 is acting in the extracellular space. Since we did not detect any increase in the phagocytic activity of the microglia in the RNF5-treated mice, we speculate that microglial phagocytosis may not be playing a significant role in tau clearance, despite being one of the well-documented mechanisms of action following passive immunotherapy with tau antibodies [20,21,28,29]. Alternatively, it may be possible that RNF5 is acting in the extracellular space to prevent the internalisation of tau seeds in the K3 mice, thus preventing the formation of insoluble tau species.…”
Section: Discussionmentioning
confidence: 99%